The digestion of fibre in herbivorous Anatidae a review - Durant, D (Wildfowl, 2013)
Numerous studies on the ability of herbivorous Anatidae to digest fibre from a variety of food types (foliage, seeds, tubers) have yielded variable results. Herbivorous ducks and geese have the capacity to digest some components of fibre (between 0% and 85%, depending on the study and the fibre com ponents analysed), in particular hem icellulose. H em icellulose may be partially digested by acid hydrolysis early in the digestive tract, and the small particles of the fluid digesta obtained may undergo a lim ited ferm entation in the caecae (with the aid of symbiotic microflora). Two sources of variation in the digestibility of fibre identified by the studies are discussed: experim ental factors (in p articular the dif.